Blocking Autophagy in Cancer-Associated Fibroblasts Supports Chemotherapy of Pancreatic Cancer Cells - Zhang, Xianbin; Schönrogge, Maria; Eichberg, Johanna; Wendt, Edgar Heinz Uwe; Kumstel, Simone; Stenzel, Jan; Lindner, Tobias; Jaster, Robert; Krause, Bernd Joachim; Vollmar, Brigitte; Zechner, Dietmar (Frontiers in Oncology, 2018)
In this study we evaluated the interaction of pancreatic cancer cells, cancer-associated fibroblasts, and distinct drugs such as α-cyano-4-hydroxycinnamate, metformin and gemcitabine. We observed that α-cyano-4-hydroxycinnamate as monotherapy or in combination with metformin could significantly induce collagen I deposition within the stromal reaction. Subsequently, we demonstrated that cancer-associated fibroblasts impaired the anti-proliferation efficacy of α-cyano-4-hydroxycinnamate, metformin and gemcitabine. Interestingly, inhibition of autophagy in these fibroblasts can augment the anti-proliferation effect of these chemotherapeutics in vitro and can reduce the tumor weight in a syngeneic pancreatic cancer model. These results suggest that inhibiting autophagy in cancer-associated fibroblasts may contribute to strategies targeting cancer.